1999
DOI: 10.1046/j.1471-4159.1999.0720461.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of a Putative Cyclic Nucleotide‐Gated Ion Channel cDNA from Limulus polyphemus

Abstract: Cyclic nucleotide-gated channels have been proposed to mediate the electrical response to light in the ventral photoreceptor cells of the horseshoe crab, Limulus polyphemus. However, a cyclic nucleotide-gated channel has not been identified from Limulus. We have cloned a putative full-length cyclic nucleotide-gated channel cDNA by screening cDNA libraries constructed from Limulus brain using a probe developed from Limulus ventral eye nerves. The putative full-length cDNA was derived from two overlapping partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Forward (OpsF1) and reverse (OpsR2) primers (Table1) based on this initial sequence were used to screen various cDNA libraries and other EST collections from Limulus. An anticipated 250-bp product with a sequence identical to the new opsin was obtained from a LE cDNA library (Smith et al, 1993), VE and adult brain cDNA libraries (Chen et al, 1999) and VE and adult CNS EST collections. Using the VE EST collection as template, the 250-bp sequence was extended with a RACE (rapid amplification of cDNA ends) strategy, using the 5Ј and 3Ј adaptor primers Lu4st11 and Lu4 TRSA (Matz, 2003) (Table1).…”
Section: Cloning Limulus Opsin5mentioning
confidence: 99%
“…Forward (OpsF1) and reverse (OpsR2) primers (Table1) based on this initial sequence were used to screen various cDNA libraries and other EST collections from Limulus. An anticipated 250-bp product with a sequence identical to the new opsin was obtained from a LE cDNA library (Smith et al, 1993), VE and adult brain cDNA libraries (Chen et al, 1999) and VE and adult CNS EST collections. Using the VE EST collection as template, the 250-bp sequence was extended with a RACE (rapid amplification of cDNA ends) strategy, using the 5Ј and 3Ј adaptor primers Lu4st11 and Lu4 TRSA (Matz, 2003) (Table1).…”
Section: Cloning Limulus Opsin5mentioning
confidence: 99%
“…2000). Our pharmacological observations and our characterization of a novel Limulus TRP channel provide a testable alternative to the proposed role of a cyclic nucleotide channel that has also been recently cloned from this system (Chen et al . 1999), and may resolve the differences in phototransduction between Limulus and Drosophila photoreceptors.…”
Section: Discussionmentioning
confidence: 85%
“…It has also been suggested that multiple second messenger pathways and channels may mediate the response in Limulus photoreceptors (Nagy 1993). The search for alternative mechanisms has led to physiological and molecular evidence for a cyclic nucleotide gated channel in the light-sensitive membrane of Limulus ventral photoreceptors (Johnson et al 1986;Bacigalupo et al 1991;Chen et al 1999Chen et al , 2001. There is pharmacological evidence for the linkage of the opening of this channel to the PI pathway via a guanylate cyclase (Garger et al 2004), but no biochemical or molecular pathway has yet been identified.…”
mentioning
confidence: 99%
“…These channels have properties similar to the light-activated channels in cell-attached patches on the R-lobe [48]. Most recently, a putative cyclic nucleotide-gated channel gene has been cloned from Limulus [22]. The mRNA for the channel is expressed in photoreceptors and the protein product was specifically localized in the R-lobe [21].…”
Section: Discussionmentioning
confidence: 99%
“…The Limulus cascade ends with the opening of cGMP-gated channels which, in this system, can be directly studied in cell-attached and excised patches [19,20]. Photoreceptor cells contain mRNA for a putative Limulus cyclic nucleotide-gated channel protein, and antibodies to the expressed protein specifically label the light-sensitive rhabdomeric lobe [21,22]. Furthermore either intracellular injection of cGMP [23,24] or elevation of cGMP by inhibition of phosphodiesterase [25,26] excites the cell.…”
Section: Introductionmentioning
confidence: 99%